Medical specialties and life expectancy: An analysis of doctors' obituaries 1997-2019 - Adam B. Brayne; Ralph P. Brayne; Alexander J. Fowler (Wiley, 2021)
Abstract Background Previous studies have found emergency medicine physicians have a reduced life expectancy compared to other doctors, using small subsets of data from the obituary section of the British Medical Journal. Technological advances now allow the entire catalogue of obituaries to be interrogated, which allows exploration of the relationship between medical specialty, age at death and cause of death in doctors. Methods Publicly available electronic records were obtained by web scraping and analysed with natural language processing algorithms. Obituaries published in the British Medical Journal between January 1997 and August 2019 were scraped and analysed for differences in age and cause of death and also relative survival analysis compared to the general U.K. population. Results Data were extracted from 8156 obituaries. The specialties with the oldest average age at death were general practitioners (80.3, SD = 12.5, n = 2508), surgeons (79.9, SD = 13.6, n = 853) and pathologists (79.8, SD = 13.8, n = 394). The specialties with the youngest average age at death were emergency physicians (58.7, SD = 23.6, n = 43), anaesthetists (75.5, SD = 16.1, n = 473) and radiologists (75.8, SD = 14.5, n = 172). Cancer was the most common cause of death and did not differ by specialty. Doctors on average have an older age at death than the general U.K. population. Conclusions A doctor's specialty has a significant association with their age at death, with general practitioners living the longest and emergency physicians the shortest, with proportionately more accidental deaths. Likely due to its recency as a separate specialty, the emergency physician group is the smallest, which may censor and falsely reduce this group's age at death. The observed increased life expectancy and the reduced cardiovascular disease in this cohort may be associated with lifestyle and socioeconomic factors.